2018
DOI: 10.1016/j.clinbiomech.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

The implementation of inertial sensors for the assessment of temporal parameters of gait in the knee arthroplasty population

Abstract: These findings suggest that inertial measurement units can be used for outside laboratory assessment (e.g. in a hospital environment) of temporal gait parameters in the knee arthroplasty population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 27 publications
(33 reference statements)
3
17
0
4
Order By: Relevance
“…Nevertheless, a recent meta-analysis [ 15 ] found that inertial sensors displayed moderate to excellent validity and reliability for mean ST parameters across a range of placements in healthy adult walking. These findings were supported by the current review, as numerous studies found a high level of validity and reliability in these parameters for adults with OA [ 19 , 30 , 37 , 54 , 57 , 67 , 77 ]. Only Item-Glatthorn et al (2012 [ 47 ]) cautioned against the use of certain parameters such as double support, walking speed, and step length.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Nevertheless, a recent meta-analysis [ 15 ] found that inertial sensors displayed moderate to excellent validity and reliability for mean ST parameters across a range of placements in healthy adult walking. These findings were supported by the current review, as numerous studies found a high level of validity and reliability in these parameters for adults with OA [ 19 , 30 , 37 , 54 , 57 , 67 , 77 ]. Only Item-Glatthorn et al (2012 [ 47 ]) cautioned against the use of certain parameters such as double support, walking speed, and step length.…”
Section: Discussionsupporting
confidence: 87%
“…The duplicate removal rendered 376 articles, which were screened at the title/abstract level. A full-text screening process of 107 articles resulted in 72 articles, and these 72 articles were included in our scoping review [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ...…”
Section: Resultsmentioning
confidence: 99%
“…For instance, De Vroey et al [3] succeeded to validate the use of IMUs with an optical motion capture system for the calculation of temporal aspects of gait in a knee arthroplasty population. Despite the excellent possibilities for the use of IMUs in motion analysis, some crucial concerns and methodological problems need to be tackled especially to use them for estimation of joint kinematics.…”
Section: Introductionmentioning
confidence: 99%
“…The IC and FC gait event times were determined using filtered mediolateral acceleration data from the shank sensor. This algorithm has been commonly applied in studies using IMU sensors to define IC and FC gait event times, both in healthy individuals and in those with pathological disorders [ 5 ], including application for patients with knee arthroplasty [ 36 ], spinal cord injuries [ 37 ], and Parkinson’s disease [ 29 ]. All of these studies have been in agreement and confirmed the validity of using the shank angular velocity to define gait events with the golden standard, such as motion capture systems or foot switches.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…All of these studies have been in agreement and confirmed the validity of using the shank angular velocity to define gait events with the golden standard, such as motion capture systems or foot switches. De Vroey et al (2018) [ 36 ] reported adequate to excellent intra-class correlation values overall for temporal gait parameters calculated using shank angular velocity and a camera system, also suggesting that IMU sensors can be used outside of laboratory assessments to examine the temporal gait parameters in the knee arthroplasty population.…”
Section: Discussion and Future Workmentioning
confidence: 99%